Logical Quantification and Plato’s Theory of Forms - Boongaling, John Ian (Aufklärung: journal of philosophy, 2015)
Contemporary philosophers find Plato’s discussion in the Sophist about the problem of negation and falsity as interesting and difficult. It is interesting in the sense that in this dialogue, and others that are considered by Plato scholars to belong to the late period dialogues, we seem to find a Plato who makes less use of the theory of Forms (a distinguishing feature of the middle period dialogues). It is difficult in the sense that It invites us to use the notational convention of modern symbolic logic to provide a coherent picture of Plato’s view. Charlton prefers a Platonizing Interpretation on the issue and quantifies over Forms (and not over concrete objects). Given this context, the paper inquires whether logical quantification is the correct (or at the very least, the best) route to pursue in order to better understand the Forms. It will also discuss the crucial role of Plato’s theory of Forms in the middle and late period dialogues in relation to knowledge and its very possibility.